PERANAN PENYULUH PERTANIAN DALAM PENGEMBANGAN GABUNGAN KELOMPOK TANI (GAPOKTAN) - Asmina Herawaty Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This study aims to determine the effect of the work program extension granted to the Joint Farmers Group (union) on the response and perception Gapoktan. This research was conducted in the village of Dolat Rayat, District Karo. This location was selected on the basis that in the district is one of the locations that have experienced Agricultural Extension and farmer groups are quite a lot and accomplished. The research was conducted. The population in this study is the Farmers Group Association (union) in the territory of the District Karo. Of each member of the group of farmers in farmer group in the village of Dolat Rayat, selected 30 respondents. Methods of data analysis using multiple regression. The results showed that the response to the program agricultural extension work is high at 53.33% correlation of test results obtained by the r value of 0.727. This means that the work program extension granted to the farmer Group Association in the research area. Socio factors have a significant effect on the response and perception Combined farmer Group Association in the research area. Socio-economic factors have a significant effect on the response and perception Combined farmer groups ( union). The level of education has a greater influence on the response farmers to agricultural extension programs in the amount of 42.30%, followed by the age of 37.10%, a land area of 27.40 % and the number of dependents of 5.30 %. Corn crop productivity in the research area 5326.83 kg/ha/year. It is still relatively low because of the potential maximum production of corn hybrids between 7-11 tonnes/ha. The amount of net income of farmers in the research area is Rp. 4.989,684,17 /ha/year or Rp. 891,470, 19/ha/month which is still relatively low when compared to the local minimum wage District Karo Rp. 1.69195 million/month. Corn farming research area deserves to be continued or efficient value Output Input Ratio (OIR) by 1.51.